Returns to Education and Female Participation Nexus: Evidence from India - Sanghamitra Kanjilal-Bhaduri; Francesco Pastore (Institute of Labor Economics (IZA), 2017)
In this paper, we make an attempt to understand whether low labour market returns to education in India are responsible for low female work participation. The National Sample Survey Office (NSSO) Employment Unemployment Survey (EUS) unit level data of India for the year 2011–12 is used to examine the relationship between educational attainment and labour market participation through gender lens. Results show that women's education has a U-shaped relationship with paid work participation. The probability to participate in the paid labour market shows an increasing trend with education levels higher than compulsory secondary schooling. The labour market returns to education are insignificant and low for lower levels of education. The returns increase significantly along with the increase in educational levels. However, females have a significant lower rate of return for each year of education as compared to men in rural and urban labour markets as well. Though it has been said that increase in female enrolment in schooling is one of the reasons of the recent declining phenomenon of female participation, but our study shows that the low returns to education is another reason for their less participation. The findings therefore suggest that, women need to be educated above secondary level to become visible in the labour market.
Keywords: J16; J21; J82; O12; O15; 330; female labour force participation; market returns to education; development; India